Reminiscence Therapy through Kidung Bali for Depression of older people living in Urban area - Sukardin, Sukardin; Suryatno, Hadi; Wayan Dewi Parwati, Ni; Made Sumartyawati, Ni (UIMA Press, 2021)
Abstract: Aging process impacted the existence of health-related problems. Depression is one of the most common health problems that occurred in older people. Effects experienced by elderly depression is an increased risk of getting various diseases. So that we need therapy as an alternative treatment for depression in the elderly. Objectives: This study aimed to determine the effect of Reminiscence therapy through Kidung Bali on the changes in depression in the elderly in Urban area. Methods: This research was a quasi-experimental study performed on 33 Elderly in Mataram. Participants were randomly selected. The Geriatric Depression Scale (GDS) questionnaire was used to collect data related to Elderly Depression. Reminiscence therapy was conducted over five days, the duration of treatment approximately 30-40 minutes each meeting. Data were analyzed using Pearson and Spearman correlation and Wilcoxon-test in SPSS 24. Results: : This study illustrated that there was a change in the Geriatric Depression Scale score. Before giving the reminiscence therapy, a mean value was 5.67, and after being given the reminiscence therapy, the mean Value changed to 3.15. Statistical test results showed the p-value <α (0.000 <0.05). Conclusion: It can be concluded that There was an effect of Reminiscence therapy through Kidung Bali to elderly depression in Urban area. Reminiscence therapy through Kidung Bali is an alternative option in reducing depression in the elderly. Keywords: Reminiscence therapy, Kidung Bali, Elderly, Depression.